Analisis faktor-faktor yang mempengaruhi pengangguran terbuka di Provinsi Jambi - Rhivna Cilviyani Rambe; Purwaka Hari Prihanto; Hardiani Hardiani (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2019)
The research as purpose: (1) To find out and analysis the development of open unemployment rates in Jambi Province; and (2) What factors influence open unemployment in Jambi Province. The method used in this study is descriptive analysis and quantitative analysis, namely multiple linier regression using data from 2000-2017. The results of this study indicate: (1) The average development of open unemployment in Jambi Province is 0,53 percent; (2) The results of data analysis show that during the period 2000-2017 GDP, wages, inflation, and investment had a positive and significant effect on open unemployment in Jambi Province. A level of labor force participation does not significantly influence open unemployment in Jambi Province. Keyword: Open Unemployment, Wages, Inflation, Investment, and Labor Force Participation Rates.